Bifidobacterium bifidum and the infant gut microbiota: an intriguing case of microbe‐host co‐evolution - Duranti, Sabrina; Lugli, Gabriele Andrea; Milani, Christian; James, Kieran; Mancabelli, Leonardo; Turroni, Francesca; Alessandri, Giulia; Mangifesta, Marta; Mancino, Walter; Ossiprandi, Maria Cristina; Iori, Alexandra; Rota, Claudio; et al. (Environmental microbiology, 2019)
Summary Bifidobacterium bifidum is reported to be among the first colonizers of the newborn's gastrointestinal tract due to its ability to metabolize human milk oligosaccharides (HMOs). In order to investigate biological features that allow this bifidobacterial species to colonize a newborn, bifidobacterial internally transcribed spacer profiling of stool samples of 50 mother‐infant dyads, as well as corresponding breastmilk samples, was performed. Hierarchical clustering based on bifidobacterial population profiles found in infant faecal samples revealed the presence of four bifidobacterial clusters or the so‐called bifidotypes. Bifidobacterium bifidum was shown to be a key member among bifidotypes, in which its presence correlate with several different bifidobacterial species retrieved in infant faecal samples. For this reason, we investigated cross‐feeding behaviour facilitated by B. bifidum on a bioreactor model using human milk as growth substrate. Transcriptional profiles of this strain were evaluated when grown on nine specific glycans typically constituting HMOs. Remarkably, these analyses suggest extensive co‐evolution with the host and other bifidobacterial species in terms of resource provision and sharing, respectively, activities that appear to support a bifidobacteria‐dominant microbiome.